Induction of Central Host Signaling Kinases during Pneumococcal Infection of Human THP-1 Cells - Kohler, Thomas P.; Scholz, Annemarie; Kiachludis, Delia; Hammerschmidt, Sven (Frontiers in Cellular and Infection Microbiology, 2016)
Streptococcus pneumoniae is a widespread colonizer of the mucosal epithelia of the upper respiratory tract of human. However, pneumococci are also responsible for numerous local as well as severe systemic infections, especially in children under the age of five and the elderly. Under certain conditions, pneumococci are able to conquer the epithelial barrier, which can lead to a dissemination of the bacteria into underlying tissues and the bloodstream. Here, specialized macrophages represent an essential part of the innate immune system against bacterial intruders. Recognition of the bacteria through different receptors on the surface of macrophages leads thereby to an uptake and elimination of bacteria. Accompanied cytokine release triggers the migration of leukocytes from peripheral blood to the site of infection, where monocytes differentiate into mature macrophages. The rearrangement of the actin cytoskeleton during phagocytosis, resulting in the engulfment of bacteria, is thereby tightly regulated by receptor-mediated phosphorylation cascades of different protein kinases. The molecular cellular processes including the modulation of central protein kinases are only partially solved. In this study, the human monocytic THP-1 cell line was used as a model system to examine the activation of Fcγ and complement receptor-independent signal cascades during infection with S. pneumoniae. Pneumococci cultured either in chemically defined or complex medium showed no significant differences in pneumococcal phagocytosis by phorbol 12-myristate 13-acetate (PMA) differentiated THP-1 cells. Double immuno-fluorescence microscopy and antibiotic protection assays demonstrated a time-dependent uptake and killing of S. pneumoniae 35A inside of macrophages. Infections of THP-1 cells in the presence of specific pharmacological inhibitors revealed a crucial role of actin polymerization and importance of the phosphoinositide 3-kinase (PI3K) and Protein kinase B (Akt) as well during bacterial uptake. The participation of essential host cell signaling kinases in pneumococcal phagocytosis was deciphered for the kinase Akt, ERK1/2 and p38 and phosphoimmunoblots showed an increased phosphorylation and thus activation upon infection with pneumococci. Taken together, this study deciphers host cell kinases in innate immune cells that are induced upon infection with pneumococci and interfere with bacterial clearance after phagocytosis.